Pengaruh Penambahan Ekstrak Kayu manis (Cinnamomum Burmanni) terhadap Sifat Kimia dan Sensori Dadih Susu Sapi - Indriani, Rita; Nealma, Samuyus; Reza Jatnika, Ahmad (Fakultas Ilmu dan Teknologi Hayati Universitas Teknologi Sumbawa, 2025)
This study aims to determine the concentration and effect of adding cinnamon extract (Cinnamomum Burmannni) on pH, air content, antioxidant content and organoleptic test in cow's milk curd. This study was conducted at the Analytical Chemistry Laboratory of the Faculty of Mathematics and Natural Sciences in May 2025. The experimental design in this study was a completely (RAL) consisting of 4 treatments and 3 replications. The treatments in this study were the addition of cinnamon extract (Cinnamomum Burmannni) P0 (control), P1 (1%), P2 (2%), P3 (3%). This study used 4800 ml of cow's milk and 72 ml of cinnamon extract. The parameters observed were pH, air content, antioxidants and organoleptic test. The results of this study indicate that the addition of cinnamon extract has a significant effect. Phpujian obtained the highest test results P2 4.98 ± 0.01a, the water content obtained the best results P0 79.32 ± 1.51a, the highest antioxidant content P3 53.78 ± 4.02a. The taste test gave the best results in the P2 treatment, the color test gave the best results in the P2 treatment, the texture test gave the best results in the P3 treatment, the aroma test gave the best treatment results were P3 and the preference level test gave the best results in the P3 treatment of cow's milk dadih with the addition of cinnamon extract.